2022
DOI: 10.3390/medicina58101402
|View full text |Cite
|
Sign up to set email alerts
|

CPAP Therapy on Depressive and Anxiety Symptoms in Patients with Moderate to Severe Obstructive Sleep Apnea Syndrome

Abstract: Backgrounds and Objectives: There is a link between sleep apnea syndrome (OSA) and depressive and anxiety symptoms, but the underlying mechanisms are not fully understood. The study aimed to determine the prevalence of these symptoms in patients with OSA and to evaluate the impact of continuous positive airway pressure (CPAP) on depression and anxiety scores. Materials and Methods: Ninety-nine consecutive new patients diagnosed with moderate or severe (apnea-hypopnea index AHI ≥ 15 events/h) OSA were accepted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…OSA is more likely in men aged 18 to 64 years with anxiety and hypertension than those with only hypertension ( 128 ). Anxiety decreased after 6 months of CPAP treatment in 1 small study ( 129 ).…”
Section: Pathophysiology and Associations Of Osa With Other Disordersmentioning
confidence: 88%
“…OSA is more likely in men aged 18 to 64 years with anxiety and hypertension than those with only hypertension ( 128 ). Anxiety decreased after 6 months of CPAP treatment in 1 small study ( 129 ).…”
Section: Pathophysiology and Associations Of Osa With Other Disordersmentioning
confidence: 88%
“…In contrast, a prior non‐randomized, noncontrolled study assessing the impact of CPAP treatment on tinnitus found that the Tinnitus Handicap Inventory scores significantly decreased with CPAP use after 3 months for 14 patients with sleep‐disorder breathing and tinnitus symptoms 55 . Multiple studies have shown improvements in depression and anxiety symptoms following CPAP use, which have been heavily linked to tinnitus 56,57 . CPAP treatment for OSA may have positive impact on mitigating bothersome tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“… 55 Multiple studies have shown improvements in depression and anxiety symptoms following CPAP use, which have been heavily linked to tinnitus. 56 , 57 CPAP treatment for OSA may have positive impact on mitigating bothersome tinnitus. Whether this is due to CPAP's improvement of tinnitus or the noise‐masking of a CPAP machine, a known treatment for tinnitus, is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In numerous retrospective and prospective evaluations, OSA has been shown to be correlated with cognitive impairment, dementia and depression [10] , [11] , [12] , [13] , [14] , [15] , [16] . Treating OSA with CPAP therapy has been shown to lead to improvement of executive function [17] and depressive symptoms [18] , [19] . These effects are so strong, that CPAP has been proposed as first line therapy in patients with OSA and depression, before starting a pharmacological treatment [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Treating OSA with CPAP therapy has been shown to lead to improvement of executive function [17] and depressive symptoms [18] , [19] . These effects are so strong, that CPAP has been proposed as first line therapy in patients with OSA and depression, before starting a pharmacological treatment [18] .…”
Section: Introductionmentioning
confidence: 99%